IDADE, PESO, MORFOMETRIA CORPORAL E PRENHEZ EM NOVILHAS NELORE DOS 16 AOS 32 MESES - Abud, Lucas Jacomini (2010)
The objective of this study was to characterize the age, weight and body morphometric measurements of Nellore heifers reared in Cerrado biome. Fifty-six heifers were experimentally exposed with bulls for determining the onset of their reproductive life. Body weight, condition and measurements of the heifers were evaluated every 60 days between 16 and 32 months of age. The following body measurements were registered: withers height, rump height, body length, head length, rump length, ear length, distance between ribs, distance from dorsal spine to belly, distance from ground to belly, head width, rump width, width between ischiums, ear width, cannon bone perimeter, tail implantation perimeter and thoracic perimeter. The average age at the onset of their reproductive life and the mean body weight were 28,74±2,81 months and 333,83±39,13 kg, respectively. Significant difference were observed for the following measurements: withers height, rump height, body length, rump length, head width, rump width, width between ischiums, tail implantation perimeter, thoracic perimeter and body condition score. Higher morphometric measurement values were observed in pregnant animals. The age in which the animals achieved the onset of their reproductive life in this study was similar to the ones described for Zebu females in the literature. In this case, more studies on genetic improvement and management alternatives are needed to anticipate the onset of the heifers´ reproductive life. The body morphometric mensuraments were higher in the pregnant heifers, indicating that the morphometric records can be an important tool to identify precocious Nellore females. The objective of this study was to characterize the age, weight and body morphometric measurements of Nellore heifers reared in Cerrado biome. Fifty-six heifers were experimentally exposed with bulls for determining the onset of their reproductive life. Body weight, condition and measurements of the heifers were evaluated every 60 days between 16 and 32 months of age. The following body measurements were registered: withers height, rump height, body length, head length, rump length, ear length, distance between ribs, distance from dorsal spine to belly, distance from ground to belly, head width, rump width, width between ischiums, ear width, cannon bone perimeter, tail implantation perimeter and thoracic perimeter. The average age at the onset of their reproductive life and the mean body weight were 28,74±2,81 months and 333,83±39,13 kg, respectively. Significant difference were observed for the following measurements: withers height, rump height, body length, rump length, head width, rump width, width between ischiums, tail implantation perimeter, thoracic perimeter and body condition score. Higher morphometric measurement values were observed in pregnant animals. The age in which the animals achieved the onset of their reproductive life in this study was similar to the ones described for Zebu females in the literature. In this case, more studies on genetic improvement and management alternatives are needed to anticipate the onset of the heifers´ reproductive life. The body morphometric mensuraments were higher in the pregnant heifers, indicating that the morphometric records can be an important tool to identify precocious Nellore females.